2006
DOI: 10.1124/jpet.106.108902
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Isolated Mouse Whole Bladder for Investigating Bladder Overactivity

Abstract: The isolated mouse whole bladder was used to study in vitro bladder overactivity evoked by intramural nerve sensitization with bradykinin, mimicking neurogenic bladder overactivity secondary to bladder inflammation. Intravesical pressure responses to intramural electrical stimulation of intramural nerves were measured under isovolumetric condition. Validation showed that carbachol produced a dose-response curve closely mirroring that observed in the isolated muscle strips and demonstrated the dual nature of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…The peak contraction pressure change of the ChR2-expressing bladder by light (6.3 mW) was comparable to those by other stimulants such as carbachol (3 μM), a cholinergic agonist, and electrical field stimulation (50 VDC with 0.1 ms pulse duration at 20 Hz) (Fig. 3e), and was within the physiological range of voiding bladder pressure (40~50 cmH 2 O) of various species, including humans1 and rodents15.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The peak contraction pressure change of the ChR2-expressing bladder by light (6.3 mW) was comparable to those by other stimulants such as carbachol (3 μM), a cholinergic agonist, and electrical field stimulation (50 VDC with 0.1 ms pulse duration at 20 Hz) (Fig. 3e), and was within the physiological range of voiding bladder pressure (40~50 cmH 2 O) of various species, including humans1 and rodents15.…”
Section: Resultssupporting
confidence: 70%
“…The stimulation parameters of EFS were 50VDC, 0.1ms pulse duration, and 20 Hz, as previously described15.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that this response is dependent mainly on depolarization of the cell membranes and an influx of extracellular Ca 2þ , and also suggest that this depolarizing response may be due to inactivation of ATP-sensitive potassium channels through muscarinic activation of protein kinase C. 49 Validation experiments showed that external application of carbachol induced a dose response curve that compares very well with that produced in isolated muscle strips. 10 There is considerable interest in the ion channels involved in generating the spontaneous activity in the detrusor. Much of this interest is driven by the need to develop drugs to treat the symptoms of bladder overactivity, which include urgency and urge incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…The bradykinin/receptors system plays an important role in normal micturition reflexes as well as in pathology (Lecci et al, 1995; Belichard et al, 1999; Lecci et al, 1999; Meini et al, 2000; Chopra et al, 2005; Fabiyi and Brading, 2006). Kinins are small peptides (8–10 amino acids) produced in plasma or in tissues at the sites of inflammation or tissue damage (Bhoola et al, 1992).…”
Section: 5 Bradykinin/receptors System In Micturition Reflex Pathwaysmentioning
confidence: 99%